Informed consent for low-risk thyroid cancer. (May 2016) - Rosenthal, M Sara; Angelos, Peter; Bible, Keith; Fassler, Cheryl Ann; Finder, Stuart; Greene, Loren Wissner; Tulchinsky, Mark
Significant barriers to informed consent surround the clinical management of adult patients with well-differentiated thyroid cancer. The literature reveals lack of disclosure surrounding clinical equipoise; confusing and conflicting terminology; and an insufficient number of prospective trials with proper ethical oversight. We provide guidance for valid consent to treatment in this population, and propose stipulative definitions for a variety of terms used in this context. Three critical areas are addressed: surgical management, radioactive iodine management and nonvalidated practice. Sound ethical frameworks for valid consent in patients with low-risk thyroid cancer include consent to observational (or 'active surveillance') research protocols, consent to nonvalidated practice and consent when there are opposing standards of care due to insufficient data and disagreement among the community of experts.